Prevalence and causes of congenital microcephaly in the absence of a Zika virus outbreak in southern Brazil - Herber,Silvani (2019)
Abstract Objective: The aim of this study was to identify the causes of congenital microcephaly in Rio Grande do Sul, a state in southern Brazil, where no ZIKV outbreak was detected, from December 2015 to December 2016, which was the period when ZIKV infection was at its peak in northeast Brazil. Methods: This was a cross-sectional study where all notifications of congenital microcephaly in the state of Rio Grande do Sul were included for analysis. Evaluation of cases followed the guidelines of the Brazilian Ministry of Health. Dysmorphological and neurological evaluations were performed by a specialized team, and genetic tests and neuroimaging were performed when clinically indicated. STORCH infections were diagnosed using standard tests. ZIKV infection was diagnosed through maternal serum RT-PCR and/or neuroimaging associated with clinical/epidemiological criteria. Results: From 153 744 registered live births in the study period, 148 cases were notified, but 90 (60.8%) of those were later excluded as "non-confirmed" microcephaly. In the 58 confirmed cases of microcephaly (prevalence = 3.8/10 000 live births), congenital infections (syphilis, toxoplasmosis, cytomegalovirus, and ZIKV) constituted the predominant etiology (50.0%), followed by isolated CNS (15.5%), and genetic syndromes (10.3%). Congenital ZIKV syndrome (CZS) with typical phenotype was diagnosed in three cases (5.2% of all confirmed microcephaly cases or 10.4% of all congenital infections). Conclusion: In Rio Grande do Sul, where no outbreak of ZIKV infection was recorded, congenital infections were the leading cause of congenital microcephaly, and the attributable risk for CZS in the etiology of microcephaly was 5.2%.